The problem of maintaining balance of liberal and conservative principles at the congresses of clergy and Laity of Southern Russia in 1917 - Yu. A. Biryukova (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the congresses of clergy and laity that took place after the February Revolution of 1917 in the South of Russia — on the Don, Stavropol and Kuban, which were the part of the movement propagated throughout the country. It marked the broad inclusion of clergy and laity in the reform of the synodal system of relations and the solution of accumulated intra-church problems. The author examines the nature of the expansion of the participation of parish clergy and laity in church administration, the participation of diocesan bishops in these processes, the question of how the participants of the congresses imagined combining these ideas with the traditional hierarchical structure of the Church. The study is based on the protocols of the congresses of the clergy and laity and the discussion of their decisions on the pages of the periodical press of that time. The author comes to the conclusion that the congresses of the South of Russia have shown a desire to unite all members of the church community, without violating the traditional right of diocesan bishops to church governance. The revolt against the episcopal authority has passed the Cossack territories. In the inclusion of lower clergy and laity in the church administration, their participants saw the implementation of the principles of conciliarity. The most important component of the reform was the inclusion of laypeople in the church administration bodies of different levels, which took place at the initiative of the clergy as a whole.